Analisis dan Simulasi Model Matematika SEIIR Terhadap Kecanduan Penggunaan TikTok pada Mahasiswa Jurusan Matematika FMIPA UNM - Muhammad Abdy (PT. Lontara Digitech Indonesia, 2026)
This study discusses the application of the SEIIR (Susceptible, Exposed, Infected 1, Infected 2, Recovered) mathematical model to analyze the phenomenon of TikTok addiction among students in the Mathematics Department, Faculty of Mathematics and Natural Sciences, Universitas Negeri Malang (UNM). The model was developed from the SEIR model by adding two addiction categories: addiction to watching and addiction to shopping on TikTok. Data were obtained through questionnaires distributed to active students in the 2022–2024 intake and analyzed using Maple 18 software. The analysis results showed that the basic reproduction number value R_0 = 1.0775, indicating that TikTok addiction has the potential to spread within the student population. Simulation results show that the number of students addicted to watching and shopping on TikTok increased at the beginning of the period, then decreased to almost zero within 12 months. Meanwhile, the number of students who stopped their addiction experienced a significant increase to more than 50% of the total population. This illustrates that TikTok addiction can decrease over time and there is a tendency for students to abandon this behavior. This study shows that the SEIIR model can be used as a mathematical approach to describe the spread of social media addiction behavior and can be a basis for consideration in developing more effective educational intervention strategies.